The causes and consequences of managerial change in Ukraine and the complementarity of reforms - Frederic Warzynski (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2000)
This paper analyses the causes of managerial change and the impact of different reforms on firm performance, using survey data from 300 Ukrainian firms. The main findings are: 1) ownership and competition are linked to managerial change: de novo firms but also privatised firms experienced less turnover than state firms, indicating an entrenchment effect. Firms with few competitors had less turnover as well. 2) Managerial change and privatisation do not appear to play a role on their own but together positively affect profitability. 3) Similarly tough competition improves profitability and productivity in privatised firms only. 4) These findings suggest that privatisation, competition and managerial change are complementary measures to improve the performance of the firm.
Keywords: D21; G34; L33; J63; 330; managerial change; competition; privatisation; firm performance